The functional and clinical relevance of childhood trauma‐related admixture of affective, anxious and psychosis symptoms. (11th May 2015) - van Nierop, M.; Bak, M.; de Graaf, R.; ten Have, M.; van Dorsselaer, S.; ,; van Winkel, R.
Abstract : Objective: Previous work has shown that across different patient samples, patients with childhood trauma are more likely to have co‐occurrence of affective, anxious and psychosis symptoms than non‐traumatized patients. However, the clinical relevance of trauma‐related admixture remains to be established. Method: We examined patients with mood disorder (NEMESIS‐2; n = 1260), anxiety disorder (NEMESIS‐2; n = 896) or psychotic disorder (GROUP; n = 532) in terms of symptom profiles, quality of life (QOL) and social functioning. Results: Results showed that mood disorder patients with both trauma and co‐occurrence of affective, anxious and psychosis symptoms had a lower QOL ( B ‐12.6, 95% CI −17.7 to −7.5, P < 0.001), more help‐seeking behaviour [odds ratio (OR) 2.5, 95% CI 1.1–5.7, P = 0.031] and higher prevalence of substance use disorders (OR 7.8, 95% CI 1.1–58.0, P = 0.044), compared with patients without trauma history and symptom admixture (Trauma−/CL−). Similar results were found in patients with an anxiety disorder. Traumatized patients with a psychotic disorder and admixture showed lower QOL ( B ‐0.6, 95% CI −0.9 to −0.4, P < 0.001), higher prevalence of drug disorders (OR 2.2, 95% CI 1.2–3.9, P = 0.008) and lower global assessment of functioning ( B ‐12.8, 95% CI −17.1 to −8.5, P < 0.001) than Trauma−/CL− patients. Conclusion: Stratification according to childhood trauma exposure thus identifies a phenotype characterized by admixture of affective, anxiety and psychotic symptoms that, when combined, has clinical relevance. Identification of functionally meaningful aetiological subgroups may aid clinical practice.